A novel electrochemical sensor based on zirconia/ordered macroporous polyaniline for ultrasensitive detection of pesticides. Issue 2 (21st November 2014) - Wang, Yonglan; Jin, Jun; Yuan, Caixia; Zhang, Fan; Ma, Linlin; Qin, Dongdong; Shan, Duoliang; Lu, Xiaoquan
Abstract : A simple and mild strategy was proposed to develop a novel electrochemical sensor based on zirconia/ordered macroporous polyaniline (ZrO2 /OMP) and further used for the detection of methyl parathion (MP), one of the organophosphate pesticides (OPPs). Abstract : A simple and mild strategy was proposed to develop a novel electrochemical sensor based on zirconia/ordered macroporous polyaniline (ZrO2 /OMP) and further used for the detection of methyl parathion (MP), one of the organophosphate pesticides (OPPs). Due to the strong affinity of phosphate groups with ZrO2 and the advantages of OMP such as high catalytic activity and good conductivity, the developed sensor showed a limit of detection as low as 2.28 × 10 −10 mol L −1 ( S / N = 3) by square-wave voltammograms, and good selectivity, acceptable reproducibility and stability. Most importantly, this novel sensor was successfully applied to detect MP in real samples of apple and cabbage. It is expected that this method has potential applications in electrochemical sensing platforms with simple, sensitive, selective and fast analysis.